Assessment of the Physicochemical and Microbiological Quality of Swimming Pool Water in Hotels in Ouagadougou, Burkina Faso - Konkobo, Mathurin P.; Palenfo, Fousséni; Savadogo, Hamidou P.; Islam, Mohammad Shahidul (European Journal of Applied Sciences, 2026)
Public swimming pools constitute health-risk environments when water treatment and monitoring are inadequate. This study aimed to assess the physicochemical and microbiological quality of water from three hotel swimming pools in Ouagadougou in order to determine compliance with current sanitary requirements. This was a descriptive study conducted in three pools selected according to their level of use, water circulation system, and chlorine treatment. Repeated water samples were collected over three days and analyzed for temperature, pH, turbidity, free chlorine, revivable bacteria, total coliforms, Escherichia coli, and staphylococci. The results showed several non-compliances, particularly in pools H1 and H2, with elevated temperatures, insufficient free chlorine levels, variable turbidity, and the presence of indicator organisms in some sampling series. Escherichia coli was not detected in any of the analyzed samples, whereas staphylococci were found in all three pools. Pool H3 generally showed better physicochemical and microbiological control than H1 and H2. These findings highlight the need to strengthen sanitary surveillance, free chlorine and pH monitoring, and maintenance of filtration systems in hotel swimming pools. They also underscore the importance of compliance with regulatory requirements and staff training for pool operation.